Description of a new Eucoryphus species from the island of Corsica, France (Diptera: Dolichopodidae, Hydrophorinae) - Pusch, Martina H.e.; Stark, Andreas; Pollet, Marc (Zootaxa, 2020)
Eucoryphus Mik is a Palaearctic genus of Dolichopodidae, previously with two described species confined to the montane and alpine zones of the European Alps. This paper describes a third species, Eucoryphus piscariviverus sp. nov., discovered in the mountains of southern Corsica. The systematic position of the genus Eucoryphus and the ecology of its species are discussed in detail and a key to males of the three species is provided.